Delleman–Oorthuys syndrome (oculocerebrocutaneous syndrome) in a Nigerian child: a case report - Badejo, Oluwakemi A. (Ther Adv Ophthalmol, 2018)
BACKGROUND: Delleman–Oorthuys syndrome, also known as oculocerebrocutaneous syndrome, is a rare congenital anomaly with ocular, cerebral and cutaneous manifestations. So far, only 40 cases have been described. CLINICAL CASE: A 3-year-old female Nigerian child with no identifiable left eyeball, multiple left-sided facial skin defects and delayed developmental milestones but otherwise uneventful medical and family history was evaluated at the Ophthalmology and Paediatric Neurosurgery in Ibadan, Nigeria. Besides the mentioned defects that were present since birth, brain imaging revealed several brain abnormalities including intracranial cysts. Global hyperreflexia and bilateral flexor plantar response were observed upon clinical examination. Left micro-ophthalmia and orbital mass were detected. A histological assessment of the orbital mass revealed it to be rudimentary ocular tissue. The diagnosis of Delleman–Oorthuys syndrome was made based on the clinico-radiological features. The patient underwent a left-sided posterior fossa cystoperitoneal shunt. The left orbital mass was enuclated and the patient is currently awaiting left eyelid reconstruction and an orbital implant and repair of the left alar nasi cleft. CONCLUSION: To our knowledge, this is the first published report of Delleman–Oorthuys syndrome in a female child of West African descent. Given the variable manifestations of Delleman–Oorthuys syndrome, and overlap with other syndromes, the Delleman–Oorthuys syndrome may be underreported. Neuroimaging of patients with cutaneous tags, orbital cysts and micro-ophthalmia could reveal more cases.